Community social vulnerability and the 340B Drug Pricing Program: Evaluating predictors of 340B participation among critical access hospital - Owsley, Kelsey M.; Karim, Saleema A. (The Journal of rural health, 2024)
Purpose The federal 340B Drug Pricing Program allows eligible hospitals, including critical access hospitals (CAHs), to obtain outpatient drugs at a discounted rate. CAHs likely benefit from 340B participation because they are often under‐resourced and serve at‐risk patient populations. The objective of this study was to understand predictors of 340B program participation among CAHs, and how participation varies with community‐level social vulnerability. Methods We used a cross‐sectional study design to assess the relationship between 340B participation in 2019 and community vulnerability status using 2018 data from the CDC's social vulnerability index (SVI) among acute care CAHs. Analyses used linear probability models adjusted for hospital‐level characteristics. Findings In bivariate analyses, CAHs participating in the 340B program had lower overall social vulnerability scores, relative to nonparticipating, eligible, and ineligible CAHs, respectively (43.8 vs. 48.7 vs. 64.7, p < 0.10). In adjusted regression models, greater community vulnerability rankings due to socioeconomic status (–0.129, p < 0.05) and minority status and language (–0.092, p < 0.05) were associated with decreased 340B participation. Higher hospital operating margin was associated with increased 340B participation (0.163, p < 0.05). Although the number of for‐profit CAHs ineligible for 340B was small, they had the highest community‐level social vulnerability score and lowest hospital operating margin on average. Conclusions CAHs located in areas of high community vulnerability are less likely to participate in the 340B program. Some vulnerable patient populations served by CAHs may be excluded from 340B program benefits.